The labor market in the UK, 2000-2019 - Benedikt Herz; Thijs Van Rens (IZA World of Labor, 2020)
Experiences during the Great Recession support the view that the UK labor market is relatively flexible. Unemployment rose less and recovered faster than in most other European economies. However, this success has been accompanied by a stagnation of productivity and wages; an open question is whether this represents a cyclical phenomenon or a structural problem. In addition, the effects of the planned exit of the UK from the EU (Brexit), which is quite possibly the greatest current threat to the stability of the UK labor market, are not yet visible in labor market statistics.
Keywords: E24; J2; 330; unemployment; productivity; UK; Brexit